Shift of bifurcation point due to noise induced parameter. (15th March 2000) - Banerjee, Sandip; Bhattacharya, Rakhi; Chakrabarti, C. G.
Abstract : The object of the paper is to see the effect of small stochastic parametric perturbation on a nonlinear interacting system exhibiting Hopf bifurcation. The method is based on the technique of Markov diffusion approximation.